Caracterización morfológica, patogénica y genética del agente causal de la antracnosis (Colletotrichum gloeosporioides) en guanábana (Annona muricata) en el Valle del Cauca - Álvarez, E.; Ospina, C.A.; Mejía de los Ríos, J.F.; Llano Rodríguez, Germán Alberto (2004)
Anthracnose, caused by the fungus Colletotrichum gloeosporioides, generates losses of up to 90% in traditionally grown soursop orchards. The pathogen attacks the leaves, branches, flowers, and fruits, producing black fruit rot, especially during the rainy season. Typical disease symptoms initially observed includes small dark specks in the tissue, followed by the formation of slightly sunken spots surrounded by a dark halo. Of 109 isolates of Colletotrichum spp. obtained from diseased crops in several production areas of Valle del Cauca, 54 were selected at random and characterized based on colony morphology, pathogenicity and polymerase chain reaction (PCR), using the specific primers ITS Ca Int2 (C. acutatum) and CgInt (C. gloeosporioides). In addition restriction enzyme digestion was performed on DNA from the internally transcribed spacer region of the ribosomal RNA gene for each strain and the genetic diversity of this population was evaluated by random amplified microsatellites (RAMs). The results showed a correlation of -0.84 between growth characteristics of isolates and pathogenicity. Slow growing isolates presenting gray mycelium, limited sporulation, and undulating relief were found to be highly pathogenic. The amplification with specific primers for C. gloeosporioides and C. acutatum generated 450-bp and 490-bp fragments, respectively, confirming the species identity. Fifty isolates were identified as C. gloeosporioides and 4 as C. acutatum. The combination of universal primers ITS1 and ITS4 generated a 580-bp fragment, which was digested by the Hae III and Rsa I restriction enzymes. The differences in restriction patterns gave rise to two groups that corresponded to each of the pathogen species. The analysis of RAMs indicated high genetic variability among isolates and made it possible to detect a relationship among pathogenic variability - colony diameter with genetic variability. These results illustrate the phenotypic and genetic diversity of Colletotrichum spp. associated with anthracnose of soursop.